PEMAHAMAN SANTRI GRIYA KHADIJAH TERHADAP WAKAF PRODUKTIF DENGAN PENDEKATAN TAKSONOMI BLOOM - Setiawan, Haryansyah; Sunan Fanani; Eko Fajar Cahyono (Jurnal Ekonomika dan Bisnis Islam, 2023)
This study aims to determine the level of understanding of Griya Khadijah students towards productive waqf in order to evaluate learning and formulate strategies in producing competent human resources. This research uses a qualitative approach with descriptive methods. The data collected came from direct interviews with all Griya Khadijah students, totaling 22 people and from documents at the end of semester exams for productive waqf subjects at Griya Khodijah Puspas Unair. In terms of analyzing, this study uses the revised version of Bloom's taxonomy understanding theory in the cognitive realm, which includes interpreting, exemplifying, classifying, summarizing, inferring, comparing, and explaining. (explaining). As well as analyzing understanding based on its level, namely high level or exploration; moderate level or interpretation; and low level or translation. As a result, five of the seven indicators show an exploratory understanding which proves that on average Griya Khadijah students have a high understanding of the concept of productive waqf. However, understanding is still not completely perfect. Griya Khadijah Santri are still at an intermediate level of understanding on measurements with interpreting and exemplifying indicators, so that more learning focus is needed on these two indicators.